A new species of Chironomus Meigen (Diptera: Chironomidae: Chironominae) from polluted streams of southeastern Brazil - Correia, Leny C.s.; Trivinho-Strixino, Susana; Michailova, Paraskeva (Zootaxa, 2006)
The larva, pupa, adults, and karyotype of Chironomus inquinatus sp. n. are described. This species lives in polluted streams in southeastern Brazil and belongs to the pseudothummi cytocomplex, with chromosome arm combinations AE, BF, CD, and G.